2008
DOI: 10.1016/j.expneurol.2007.10.015
|View full text |Cite
|
Sign up to set email alerts
|

The antidepressant sertraline improves the phenotype, promotes neurogenesis and increases BDNF levels in the R6/2 Huntington's disease mouse model

Abstract: Huntington's disease (HD) is an inherited progressive neurodegenerative disorder characterized by progressive movement, psychiatric and cognitive disturbances. Previous studies have indicated that HD pathogenesis may be mediated in part by loss of brain derived neurotrophic factor (BDNF). Antidepressants selectively blocking serotonin reuptake can increase BDNF levels, and also may increase neurogenesis. Here we report that an SSRI antidepressant, sertraline, prolongs survival, improves motor performance, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
94
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(107 citation statements)
references
References 62 publications
(87 reference statements)
10
94
3
Order By: Relevance
“…Importantly, fluoxetine also rescued the neurogenic process in the R6/1 DG, strongly supporting the hypothesis that modulation of hippocampal neurogenesis might improve cognitive function in HD (Grote et al, 2005). In a more recent study, Peng et al (2008) tested the potential benefitial effects of another serotonine reuptake inhibitor sertraline in R6/2 mice. Sertraline treatment was initiated when the mice were 6 weeks of age and was shown to prolong R6/2 survival in a dosedependent manner (5 mg/kg by 13%; 10 mg/kg by 20%) but had no effect on the loss of body weight.…”
Section: Therapies Aimed To Restore Neurogenesismentioning
confidence: 53%
“…Importantly, fluoxetine also rescued the neurogenic process in the R6/1 DG, strongly supporting the hypothesis that modulation of hippocampal neurogenesis might improve cognitive function in HD (Grote et al, 2005). In a more recent study, Peng et al (2008) tested the potential benefitial effects of another serotonine reuptake inhibitor sertraline in R6/2 mice. Sertraline treatment was initiated when the mice were 6 weeks of age and was shown to prolong R6/2 survival in a dosedependent manner (5 mg/kg by 13%; 10 mg/kg by 20%) but had no effect on the loss of body weight.…”
Section: Therapies Aimed To Restore Neurogenesismentioning
confidence: 53%
“…This resulted in a reduction of newly generated neurons, although, in most reports, neuronal differentiation was not compromised. Several studies also observed a reduced number of neuroblasts and immature neurons (Kohl et al 2007;Peng et al 2008;Fedele et al 2011).…”
Section: Adult Neurogenesis In Transgenic Animal Models Of Hdmentioning
confidence: 99%
“…However, these studies did not assess protein levels, and chronic treatment with antidepressant drugs is required to up-regulate BDNF protein in adult mice or rats (Kozisek et al, 2008;Peng et al, 2008). It is possible that AMPH plus exercise increased mRNA for BDNF, but translation to the BDNF protein did not occur with the combined treatment.…”
Section: Effects Of Combined Treatment Of Voluntary Exercise and Amphmentioning
confidence: 99%
“…Transmitter depletion studies have shown that norepinephrine (NE) is necessary for voluntary wheel-running to up-regulate BDNF mRNA in the hippocampus (Garcia et al, 2003). Anti-depressant drugs, which increase synaptic levels of NE and 5-HT, have been reported to increase levels of hippocampal BDNF mRNA (Nibuya et al, 1995) and protein (Peng et al, 2008;Kozisek et al, 2008). In addition, anti-depressant drugs strengthen BDNF mRNA up-regulation when given in combination with exercise (Russo-Neustadt et al, 1999.…”
mentioning
confidence: 99%